A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India - Rachana, R.r.; Varatharajan, R. (Zootaxa, 2017)
Thrips laurencei sp.n. is described from specimens collected on flowers of Hydrangea macrophylla in Western Ghats range of Tamil Nadu, India. This new species shows sexual dimorphism in colour, with the females brownish yellow with brown shadings but the males uniformly yellow.